Contar para ocultar(-se): o funcionamento do silêncio na/pela formulação de Javier Marías em “Amanhã, na batalha, pensa em mim” - Santos, Júlio César Martins (Universidade Federal de São Carlos, 2024)
This Master’s Thesis uses as material for analysis the literary work “Tomorrow, in battle, think on me” (1994), by the Spanish writer Javier Marías (1952-2022). Anchored by the theory of Discourse Analysis, by Pêcheux and Orlandi, it seeks to understand how silence works in/through the author's formulation in this work. Silence and formulation, in turn, are notions that are very important to Discourse Analysis and that were worked on here under the perspective of the work of Orlandi (2012a, 2012b, 2012c, 2015). Divided into three chapters, it refers to a thematic structure that observes fundamental moments for the narrative, namely: Death, Siege and Unveiling. From this organization, a dialogue was established with theory to construct the analysis device in order to relate the passages described in the novel to the conditions of production of the work, that is, to the socio-historical, ideological aspects and constitutive exteriority. In this way, the Excerpts produced focused on recurring linguistic functions, in the syntactic and semantic spheres, such as negation, appositive enumerations and repetitions. Given these Excerpts, it was possible to discuss issues relating mainly to Spanish society in the 20th century, especially with regard to the consequences of the Spanish Civil War (1937-1939), the subsequent dictatorial regime implemented by General Francisco Franco (1939-1975), the democratic transition at the end of the dictatorship and the final decades of the millennium, the period in which the plot develops. Thus, the different types of silence described by Orlandi (2015), namely, founder and the politics of silence – subdivided into constitutive and local silence – appear in the work in order to touch on the still unhealed wounds of the traumatic experiences that occurred in Spain during the last century, since the meanings produced in the tension between telling and not telling refer to the trivialization of violence and death, constant persecution and surveillance experienced over decades of repression in confrontation with the subsequent political openness and the unavoidable change of times brought about by technological revolution announced and actually carried out. The subjects of these times, then, had to deal with these two poles: the trauma of the past and the tension of the future. The Mariasian formulation, characterized by long periods, serves, this time, as an observation and listening post not only for its elaborate imagetic constructions, but also for what it allows us to glimpse through the clues and subtle traces left by silent/in what is silenced.
Telling to hide(-oneself): the functioning of silence in/through Javier Marías’ formulation in “Tomorrow in battle think on me”
Keywords: Silêncio; Formulação; Análise de discurso; Literatura; Guerra Civil Espanhola; Ditadura franquista; Javier Marías; Silence; Formulation; Discourse analysis; Spanish Civil War; Franco dictatorship; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES